Analisis Tantangan dan Peluang Ekonomi Digital dalam Mendorong Pertumbuhan Ekonomi Berkelanjutan di Indonesia - Sabilayana Sabilayana; Andria Zulfa; Lia Nazliana Nasution (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
The digital economy plays a crucial role in driving global economic growth, including in Indonesia. However, the rapid development of digital technology also presents challenges, such as thei digital divide and uneven infrastructure. This study aimsi to analyze the impact of thei digital economy on Indonesia's economic growth using the Autoregressivei Distributed Lag (ARDL) model. The analysis results show that the Digital Divide and Digital Skills havei a negativei impact on Gross Domestic Product (GDP) in the short term, while Internet Penetration and E-commerce have a positive but insignificant impact. In the long term, these variables do not significantlyi affect GDP. These findings indicatei that although digital technology has potential, its impact is limited by factors such as unequal infrastructure access and low digital skills. Thei government needs to strengthen digital infrastructure, digital skills, and e-commerce adoption, particularly in the Small and Medium Enterprises (SMEs) sector.